A holistic approach to managing cardio-kidney metabolic syndrome: insights and recommendations from the Italian perspective - Iacoviello, Massimo; Gori, Mauro; Grandaliano, Giuseppe; Minutolo, Roberto; Pitocco, Dario; Trevisan, Roberto (Frontiers in Cardiovascular Medicine, 2025)
Cardio-kidney metabolic (CKM) syndrome represents a complex and circular interplay of cardiovascular, renal, and metabolic dysfunctions, significantly contributing to global morbidity and mortality. This expert opinion synthesizes insights from a panel of Italian specialists in cardiology, nephrology, and diabetology, advocating for a holistic and integrated framework for CKM management. The recommendations underline the critical need for early identification and stratification of CKM stages, fostering an interdisciplinary approach that bridges specialties and ensures comprehensive care. Emphasizing innovative pathways for collaboration, including dynamic referral protocols, telemedicine, and shared decision-making, the proposed strategies aim to overcome structural and organizational barriers in healthcare. By promoting a unified approach, the framework seeks to streamline CKM care, enhance communication among specialists, and improve the coordination of services. This holistic strategy represents a pivotal step toward mitigating disease progression, improving clinical outcomes, and enhancing the quality of life for patients with CKM syndrome.